EXTENDING THE THEORY OF PLANNED BEHAVIOR TO PREDICT REPURCHASE INTENTION AND REUSABLE BEHAVIOR AMONG GENERATION Z - Devina Kusuma Sentosa; Michael Ricky Sondak (RADJA PUBLIKA, 2026)
This study analyzes the determinants of sustainable consumption behavior among Indonesian Generation Z by extending the Theory of Planned Behavior with Pro-Environmental Self-Identity and Conspicuous Conservation. It examines personal identity, social pressure, perceived behavioral control, and environmental display motives regarding repurchase intention and actual product reuse. Using a quantitative online survey, data were collected from 13-28-year-olds in Indonesia with tumbler experience and analyzed through Structural Equation Modeling. Results indicate that Pro-Environmental Self-Identity strengthens Subjective Norms, while Perceived Behavioral Control is the primary predictor for Repurchase Intention and Reusable Use Behavior. Conversely, Subjective Norms show minimal impact on Repurchase Intention. Conspicuous Conservation has an inconclusive effect on the interaction between Subjective Norms and Repurchase Intention. These findings suggest that for Indonesian Generation Z, personal values and individual self-control outweigh external social pressures in driving sustainable behavior. The study highlights the necessity of developing sustainable consumption practices that minimize barriers related to self-identity and individual agency to foster effective behavioral change.